The Urgency of Citizenship Education In The Contemporary Era - Sara Anatasya; Ayrin Ariyanti; Dita Ramadhani (Lembaga Studi Agama dan Masyarakat Aceh, 2025)
Citizenship Education (PKn) plays an important role in building the identity and character of society in the contemporary era which is marked by globalization and technological progress. This article examines the urgency of Civics in the formal and non-formal education curriculum in Indonesia, exploring its meaning, objectives and functions in forming intelligent, responsible and integrity citizens. Through the Pancasila ideology approach, this education seeks to make the nation's life more intelligent and develop individual potential to become democratic citizens. In the context of the digital era, citizenship education is very important to instill the values of tolerance, love of the country, and awareness of the rights and obligations as citizens. Apart from that, Civics is expected to increase people's active participation in national and state life. This research confirms that strengthening citizenship education at all levels of education is the key to preparing future generations who are able to face social and political challenges, and contribute positively to the nation's progress